Tailoring defect chemistry at interfaces for promoted oxygen reduction reaction kinetics. Issue 44 (6th November 2020) - Kim, Seo Ju; Koo, Ja Yang; Mun, Taeeun; Choi, Mingi; Lee, Wonyoung
Abstract : Engineering the defect chemistry at the interface between the electrolyte and the electrode is crucial to facilitate oxygen reduction reaction, thereby improve the electrochemical performance of intermediate temperature solid oxide fuel cells. Abstract : The engineering of the defect concentration and distribution at the interface between the electrolyte and the cathode of intermediate temperature-solid oxide fuel cells (IT-SOFCs) is important because oxygen reduction reactions (ORRs) associated with the defects are typically the most sluggish, thereby determining the electrochemical performance. In this study, we modified the interfaces between an electrolyte (yttria-stabilized zirconia, YSZ) and cathode (La1− x Sr x MnO3− δ, LSM) using a wet chemical-based infiltration technique. The surface of the porous YSZ scaffold was conformally coated with an infiltrated YSZ layer with a thickness of 5–8 nm, a controlled doping ratio from 0 to 20 mol% Y2 O3, and, correspondingly, the oxygen vacancy concentration. The strong correlation between Y2 O3 mol% and the electrode electrochemical impedance confirmed that the enriched oxygen vacancies at the interfaces between the electrolyte and the cathode can significantly promote the ORR kinetics with the extended and active reaction sites. The infiltrated cell with an optimized doping ratio of 12 mol% Y2 O3 exhibited a 10.16 times reduced electrode area specific resistance of 0.034 Ω cm 2 and 2.97 times increased peak power density of 2.23 W cm −2 at 750 °C compared with the non-infiltrated cell, maintaining the microstructural, chemical, and electrochemical properties for 200 h at 750 °C. Our results demonstrate that the relatively simple wet chemical process can be used to fully utilize the microstructures at the interfaces between the electrolyte and the cathode for promoted ORR kinetics in the IT regime.